If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4x+6=0.5(5+30)
We simplify the equation to the form, which is simple to understand
-4x+6=0.5(5+30)
Simplifying terms in parentheses
-4x+6=0.5*(+35)
Reorder the terms in parentheses
-4x+6=+(+17.5)
Remove unnecessary parentheses
-4x+6=+17.5
We move all terms containing x to the left and all other terms to the right.
-4x=+17.5-6
We simplify left and right side of the equation.
-4x=+11.5
We divide both sides of the equation by -4 to get x.
x=-2.875
| s=-(19) | | 10x-2x=8+2x-2x | | X(X+7)-2=8 | | 7z-z-5z=11 | | 8p+13=5-13 | | (2g)(7g)= | | 9q-13+3(q+8)=7 | | -28+15n-22z=31 | | 9q-13+3(a+8)=7 | | m-4/9=-2,67/90 | | 3x+2738=6714 | | 9x-7y=31 | | 3x+2238=6714 | | 28x-4=49x^2 | | 4(-7x+5)-2x=5 | | 4x-10=-4+22 | | 28x-4=-49x^2 | | log(9x-8)=0 | | 8x-2y=-2 | | 90=5x-2x-30 | | Ax^3-ay^3-bx^3+by^3=0 | | 5(m-1)=10 | | 11x+2y=-12 | | xq+1n=300 | | 7x+2+5x=-10 | | 2m-6=4+2m | | 12x-15+2x+4=24 | | 26=(5-4)f | | 3x^2+24+18x=0 | | 4x+6y=-2 | | 18(7-2x)=7+2x | | 3x+4(-x-8)=-42 |